Recombinant Mal d 1 facilitates sublingual challenge tests of birch pollen‐allergic patients with apple allergy. Issue 2 (6th November 2015) - Kinaciyan, T.; Nagl, B.; Faustmann, S.; Kopp, S.; Wolkersdorfer, M.; Bohle, B.
Abstract : It is still unclear whether allergen‐specific immunotherapy (AIT) with birch pollen improves birch pollen‐related food allergy. One reason for this may be the lack of standardized tests to assess clinical reactions to birch pollen‐related foods, for example apple. We tested the applicability of recombinant (r) Mal d 1, the Bet v 1‐homolog in apple, for oral challenge tests. Increasing concentrations of rMal d 1 in 0.9% NaCl were sublingually administered to 72 birch pollen‐allergic patients with apple allergy. The dose of 1.6 μg induced oral allergy syndromes in 26.4%, 3.2 μg in 15.3%, 6.3 μg in 27.8%, 12.5 μg in 8.3%, 25 μg in 11.1%, and 50 μg in 4.2% of the patients. No severe reactions occurred. None of the patients reacted to 0.9% NaCl alone. Sublingual administration of 50 μg of rMal d 1 induced no reactions in three nonallergic individuals. Our approach allows straight forward, dose‐defined sublingual challenge tests in a high number of birch pollen‐allergic patients that inter alia can be applied to evaluate the therapeutic efficacy of birch pollen AIT on birch pollen‐related food allergy.